Practice Field Experience Integrated In Quality Improvement of Teacher - Rosyidah, Binti (STAI Miftahul Ula Nganjuk, 2016)
: Considering on the Indonesian Teacher and Lecturer Act, every Indonesian teacher needs to have a teacher certification. Indeed, it is a good opportunity as well as a challenge for every university, the which is conducting teacher training program, to have qualified graduates. As a qualified teacher, he must have four competencies concerning pedagogy, attitude, personal, and social. The question that may Arise is